Modulation of cellulase activity by lignin-related compounds. (June 2020) - Oliveira, Dyoni M.; Hoshino, Érica P.; Mota, Thatiane R.; Marchiosi, Rogério; Ferrarese-Filho, Osvaldo; dos Santos, Wanderley D.
Abstract: Pretreatment of lignocellulosic biomass generates a wide variety of lignin-related compounds (LRCs) derived from lignin depolymerization, which inhibit the enzymatic saccharification. Here, the effects of different LRCs were evaluated on cellulase activity for the hydrolysis of microcrystalline cellulose. Maximum activation of 110% on microcrystalline cellulose conversion by cellulases was observed with 30 mM syringic acid, whereas 20 mM ferulic acid increased it by 68%. Conversely, maximum inhibition of 40% was observed with 50 mM syringaldehyde. Furthermore, all phenolic acids had their maximum stimulatory effects on cellulase activity before the first 4 h of enzymatic hydrolysis, while syringaldehyde had the maximum inhibition after 12 h of hydrolysis. Activation of cellulases by phenolic acids emerges as a potential tool for lignocellulosic biomass processing for bioenergy and biorefinery. Highlights: Syringic and ferulic acid increase the conversion of cellulose to reducing sugars. Syringaldehyde reduces the cellulose depolymerization by cellulases. Phenolic acids may be potential tools for improved lignocellulose bioconversion.